The Role of Concession Agreements in Regional Economic Development: A Case Study of Binjai Regency - Habib Rizieq; Sayidina Aditya Prayogi; Iskandar Muda (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
This study investigates the trends and fiscal implications of locally generated revenue (PAD) and concession revenues in Binjai Regency from 2019 to 2023, focusing on the role of concession agreements in revenue diversification and regional economic development. Using a descriptive qualtitative approach, official financial data were analyzed to assess growth rates, revenue contributions, and reinvestment effects. Results show that PAD grew steadily from IDR 200 billion in 2019 to IDR 270 billion in 2023, while concession revenues increased more sharply from IDR 25 billion to IDR 40 billion, raising their share relative to PAD from 12.5% to 14.8%. Each additional IDR 1 billion in concession revenue is associated with approximately IDR 0.75 billion in infrastructure investment, highlighting its strategic contribution to local development. The findings indicate that concession agreements are increasingly significant in enhancing fiscal sustainability, mobilizing private investment, and supporting infrastructure projects. Effective governance, transparency, and institutional capacity are essential to maximize their socioeconomic impact. This study provides evidence-based insights for local policymakers to optimize concession management and strengthen Binjai Regency’s fiscal strategy.